Analysis of Online Customer Reviews and Perceived Price in Creating Purchase Intention - Herawati, Heny; Gustina, Dian; Santhuso, Agus; Febrianti, Reni (Universitas Mohammad Husni Thamrin, 2025)
E-commerce is a website that promotes services or products online. E-commerce in Indonesia, which utilizes internet access, includes sites that offer online stores, a rapidly growing online sales mix. Sophee is one of the most popular online shops in Indonesia for purchasing various fashion products and accessories. This study aims to analyze Online Customer Review and Perceived Price in creating Purchase Intention on Elisaberth Products (Case Study on Consumers of Local Fashion Brand Elisaberth in Bandung)”. The sample in this study amounted to 120 respondents. This study uses validity test, reliability test. The analysis in this study uses multiple regression analysis, multiple correlation analysis, coefficient of determination and hypothesis test. The results of the t test show that the Online Customer Review variable (X1) has no significant effect on Purchase Intention (Y) with a calculated t value < t table (-0.813 < 1.98045) and a sig value > a value (0.418 > 0.05) and Price Perception (X2) has a significant effect on Purchase Intention (Y) with a calculated t value > t table (8.713 > 1.98045) and a sig value < a value (0.000 < 0.05). The correlation value is 0.662 which means it shows a relationship the strong one. The coefficient of determination given by Online Customer Review (X1) and Perceived Price (X2) on Purchase Interest (Y) is 43.8% and the remaining 56.2% is influenced by other factors that were not analyzed.